Reconstruction of a large perineal defect after radical oncological pelvic exenteration in a patient with anal cancer: an interdisciplinary approach and literature review - Sabagh, Mohammad Sadegh; Cordts, Tomke; Sabetkish, Nastaran; Polychronidis, Georgios; Erhart, Philipp; Böcker, Arne Hendrik; Vogelpohl, Julian; Saeedi, Mohammed al (Microsurgery, 2025)
Introduction Recurrent anal cancer (AC) often requires surgical intervention, especially when large perineal defects must be reconstructed. These cases are complicated by poor tissue vascularity and comorbid conditions such as peripheral arterial disease (PAD). Methods We report the case of a 64-year-old male with PAD and recurrent AC, presenting with a large perineal defect following radical pelvic exenteration. Preoperative iliac artery stenting was performed to ensure adequate perfusion. Surgical reconstruction was conducted in two stages: first, a vertical rectus abdominis myocutaneous (VRAM) flap (7 × 15 cm) for pelvic floor coverage, followed by a free latissimus dorsi (LD) flap (17 × 30 cm) anastomosed to the superior gluteal vessels. Results Postoperative recovery was uneventful. Three vacuum-assisted closures were performed, and the patient was discharged 6 weeks postoperatively. At 6-month follow-up, the flap remained stable with no complications. Conclusion This case underscores the importance of preoperative vascular optimization and a staged surgical strategy when addressing large, complex perineal defects. Multidisciplinary collaboration is critical for achieving optimal outcomes.